Evaluation of limit strain and temperature history in hot stamping of advanced high strength steels (AHSS). (August 2017) - Ma, B.L.; Wan, M.; Li, X.J.; Wu, X.D.; Diao, S.K.
Highlights: A novel approach was developed to predicting the forming limit and temperature variation. The predicted FLC was characterized by the inconsistency in the temperature state of each limit strain pair. The temperature history was theoretically demonstrated as the factor improving the sheet forming limit. Abstract: The forming limit curve (FLC) provides a convenient way to forecasting the failure of metallic sheet in stamping process. In this paper, the FLC in hot stamping of the advanced high strength steels was evaluated through applying the M–K model and Hill 48 criterion with the consideration of the sheet temperature history. The temperature variation and the limit strains of the deformed sheet in the Nakazima test were both experimentally and theoretically studied. The comparison between the experimental and theoretical results in terms of temperature history and limit strain revealed that the predicted FLC, which was dissimilar to the conventional one under the isothermal condition, could well fitted the experimental data. The effect of the temperature history on sheet formability was theoretically demonstrated, the improvement of the forming limit was interpreted through comparing the limit major strains in different temperature histories and strain states. The results illustrated that the temperature history made the limit major strain in balanced biaxial strain state increasing by 12.7%. Graphical abstract: